2023
DOI: 10.1530/ec-22-0459
|View full text |Cite
|
Sign up to set email alerts
|

NEDD4L facilitates granulosa cell ferroptosis by promoting GPX4 ubiquitination and degradation

Abstract: Background: Polycystic ovary syndrome (PCOS) is an androgen disorder and ovarian dysfunction disease in women of reproductive age. The cell death of granulosa cells plays an important role in the development of PCOS. However, the mechanism of granulosa cell death is still unclear. Methods: In the current study, NEDD4L was found to be elevated in PCOS GEO databases and mouse models. The cell viability was analyzed by CCK-8 and FDA staining. The expression of ferroptosis markers was assessed by Elisa and immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…GSH depletion is considered a fundamental characteristic of ferroptosis [ 24 ]. Research has shown that a decrease in GSH levels promotes ferroptosis in GCs [ 25 ]. In our study investigating the regulation of oar-miR-134-3p expression, we discovered its significant negative regulation of HMOX1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…GSH depletion is considered a fundamental characteristic of ferroptosis [ 24 ]. Research has shown that a decrease in GSH levels promotes ferroptosis in GCs [ 25 ]. In our study investigating the regulation of oar-miR-134-3p expression, we discovered its significant negative regulation of HMOX1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, several inducers of the degradation pathways of GPX4 could also be increased. Specifically, Mn 2+ could enhance the expression of NEDD4 like E3 ubiquitin protein ligase (NEDD4L) [ 88 ], an E3 ligase, which was recently found to mediate GPX4 degradation through ubiquitin proteasome system (UPS) [ 89 ]. Heat shock protein family A (Hsp70) member 8 (HSPA8), lysosomal associated membrane protein 2 (LAMP2A), and heat shock protein 90 (HSP90), promoting chaperone-mediated autophagy (CMA)-mediated GPX4 degradation, all could be increased by ZIP8 transported ions [ [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] ].…”
Section: Discussionmentioning
confidence: 99%
“…NEDD4L belongs to the NEDD4 subfamily of ubiquitin ligases and targets a wide array of substrates, including ions, neurotransmitter channels, growth factor receptors, signaling molecules, and tight junction molecules [38] . Importantly, NEDD4L is associated with cardiovascular disease, especially coronary events [38,39] , and contributes to ferroptosis in granulocytes, cardiomyocytes, and cancer cells [27][28][29] . In this study, we observed that overexpression of NEDD4L counteracted the inhibition of ferroptosis caused by SGK1 knockdown, suggesting a regulatory relationship between SGK1 and NEDD4L in MAECs.…”
Section: Discussionmentioning
confidence: 99%
“…5D, with the minimum required interaction score set to the highest con dence level (0.9), SGK1 potentially interacts with 10 proteins, including RICTOR, MAPKAP1, MTOR, TSC22D3, PDPK1, KCNJ1, NEDD4L, FOXO3, FOXO1 and FOXO4. Notably, NEDD4L contributes to ferroptosis in multiple cell types [27][28][29] . It was hypothesized that the SGK1-mediated ferroptosis of MAECs might be associated with NEDD4L.…”
Section: The Nedd4l and Nf-κb Pathways Are Downstream Of Sgk1-mediate...mentioning
confidence: 99%